2016
DOI: 10.1016/j.elecom.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical kinetics of nanostructure LiFePO 4 /graphitic carbon electrodes

Abstract: a b s t r a c tLithium cation insertion/deinsertion reaction kinetics in a LiFePO 4 (LFP)/graphitic carbon composite material were electrochemically studied with a cavity microelectrode (CME). The LFP/graphitic carbon composite has a core LFP (crystalline/amorphous)/graphitic carbon shell structure. In the crystalline and amorphous LFP phase, different reaction mechanisms were observed and characterized. While the reaction mechanism in the crystalline LFP phase is controlled by Li + diffusion, the amorphous LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…Besides, the upshift of D- and G-bands indicated a charge transfer between the carbon host and the iodide species [23]. From the foregoing, it is clear that activated carbon can not only be used for storage charge at the EDL just like other reported materials [39,40,41], but it can also be used to design battery-like electrodes, similar to some of the previously reported materials [42,43,44,45,46,47].…”
Section: Introductionsupporting
confidence: 57%
“…Besides, the upshift of D- and G-bands indicated a charge transfer between the carbon host and the iodide species [23]. From the foregoing, it is clear that activated carbon can not only be used for storage charge at the EDL just like other reported materials [39,40,41], but it can also be used to design battery-like electrodes, similar to some of the previously reported materials [42,43,44,45,46,47].…”
Section: Introductionsupporting
confidence: 57%
“…Therefore, smooth diffusion pathways through the solid are created, allowing even strongly interacting divalent magnesium ions to move through the solid phase. Our previous report demonstrated that the redox reaction in noncrystalline components exhibits no diffusion limitation within a large potential scan rate range . Here, the UC process results in nano-FePO 4 particles with a noncrystalline structure embedded in graphitic carbon, which provides an efficient environment for reversible electrochemical insertion and deinsertion of magnesium ions.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report demonstrated that the redox reaction in noncrystalline components exhibits no diffusion limitation within a large potential scan rate range. 50 Here, the UC process results in nano-FePO 4 particles with a noncrystalline structure embedded in graphitic carbon, which provides an efficient environment for reversible electrochemical insertion and deinsertion of magnesium ions. However, as shown in Figure 3a, the large hysteresis is still observed for magnesium charge−discharge, where the potential change at the beginning of the charging (magnesium deinsertion process) is obvious.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Such nanocrystal composites can store and deliver energy at the highest rate attained to this date. In the following sections, we show two additional examples of uc-treated materials, Li 3 VO 4 (LVO) 8,10 and LiFePO 4 (LFP) 11,12 as negative and positive electrode materials for the SRC, respectively. We successfully transformed these two materials with typical battery characteristics into pseudocapacitive/ ultrafast materials via ultracentrifugation.…”
Section: Key Processing Technology: Ultracentrifugationmentioning
confidence: 99%
“…4c-d). 12 The electrochemical analysis shows two different behaviors and kinetic regimes in the core LFP (amorphous and crystalline). A surface charge storage pseudocapacitive mechanism drives the kinetics in the amorphous LFP phase containing Fe 3+ defects, while the Li + intercalation in the core crystalline LFP phase is a diffusion-limited process at a high scan rate (>120 mV s ¹1 ).…”
Section: High Rate Positive Electrode: Lifepo 4 (Lfp)mentioning
confidence: 99%